2017
DOI: 10.1017/s0033291716003305
|View full text |Cite
|
Sign up to set email alerts
|

Increased fronto-striatal reward prediction errors moderate decision making in obsessive–compulsive disorder

Abstract: Background: Obsessive-compulsive disorder (OCD) has been linked to functional

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
71
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 92 publications
26
71
6
Order By: Relevance
“…One previous study of reward anticipation (not learning) showed nucleus accumbens dysfunction in OCD (26). Here, we report an overactivation in the nucleus accumbens responses to positive prediction errors in OCD, consistent with prior data showing overactivation in OCD across error tasks and brain regions (38; 39) and in line with results from Hauser and colleagues (31), who showed excessive striatal reward prediction errors in OCD during reversal learning.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…One previous study of reward anticipation (not learning) showed nucleus accumbens dysfunction in OCD (26). Here, we report an overactivation in the nucleus accumbens responses to positive prediction errors in OCD, consistent with prior data showing overactivation in OCD across error tasks and brain regions (38; 39) and in line with results from Hauser and colleagues (31), who showed excessive striatal reward prediction errors in OCD during reversal learning.…”
Section: Discussionsupporting
confidence: 93%
“…We found no significant correlations between anterior cingulate prediction error signals and a general OCD symptom score; this lack of association is in accordance with the results from the only other fMRI study of reward prediction error in OCD (31). However, we did demonstrate an association between anterior cingulate negative prediction error signal with self-perceived 'self-regulation': driven by associations with subcomponents of difficulty in triggering behavioral change, searching for options, and implementing a plan.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to addiction disorders (Curtis and Davis, 2014), compulsive behaviors represent a loss of control over habits, which creates pathological courses of behaviors (Jentsch et al, 2014). Impairment in the reward system can change decision making and learning through the Reward Prediction Error (RPE) that includes the pros and cons of the behavioral outcomes (Benton, 2010; Hauser et al, 2017). The study of Oswald et al (2011) investigated, in rats, the maladaptive situation in which repeated intake of PF occurs along with knowledge that an aversive outcome is likely to follow.…”
Section: Introductionmentioning
confidence: 99%